Capital markets - Bairan, Bonifacio P. (Manila : Unlimited Books Library Services & Publishing, Inc., 2024)
"In the intricate tapestry of global economics, capital markets emerge as the vibrant threads weaving together the aspirations, risks, and innovations that define our financial landscape. The allure of capital markets lies in their ability to transcend borders, connecting investors and enterprises in a dance of risk and reward. As we embark on this exploration, we delve into the essence of equity markets, where stocks become the currency of corporate dreams, and investors navigate the ebb and flow of market sentiments."
Includes bibliography.
English.
Keywords: Capital market; Finance; Capital finance